The Dynamics of Islamic Education Learning Model Implementation: An Analysis of the Gap Between Lesson Plans and Classroom Practice - Akhmad Umam Khanani; Harisatunisa Harisatunisa (The Future of Education Journal, 2026)
This study was motivated by the discrepancy between the instructional models outlined in the Islamic Religious Education (IRE) lesson plans and their actual implementation in the classroom. IRE instruction is often perceived as monotonous and disconnected from students' real-life experiences, while teachers face challenges arising from students' diverse educational backgrounds and their limited foundational knowledge of Islam. This exploratory qualitative study aims to provide an in-depth analysis of the implementation of IRE instructional models, the rationale for their selection, their classroom application, and the challenges encountered during implementation. The research participant was a Grade 10 Islamic Religious Education teacher in the Computer and Network Engineering (CNE) program at SMK Ma'arif NU 1 Ajibarang. Data were collected from January to May 2026 through in-depth interviews and document analysis, and were analyzed using the stages of data reduction, data display, and conclusion drawing. The findings indicate that the teacher actively implemented three primary instructional models: Group Investigation (GI) for History and Moral Education (Akhlak), Problem-Based Learning (PBL) for Islamic Creed (Aqidah) to address the decline in religious practice in the digital era, and Project-Based Learning (PjBL) for Islamic Jurisprudence (Fiqh) and Qur'an–Hadith studies. However, a significant gap remained between the lesson plans and actual classroom practice. The teacher was required to demonstrate a high degree of flexibility in responding to students' limited Qur'an reading proficiency, insufficient religious knowledge, and time constraints caused by unexpected school activities. The study concludes that the implementation of IRE instructional models at SMK Ma'arif NU 1 Ajibarang is dynamic, prioritizing students' needs and instructional flexibility over rigid administrative compliance.